A functional study of the global transcriptional regulator PadR from a strain Streptomyces fradiae‐nitR+bld, resistant to nitrone‐oligomycin. (2nd July 2018) - Vatlin, Aleksey A.; Bekker, Olga B.; Lysenkova, Ludmila N.; Shchekotikhin, Andrey E.; Danilenko, Valery N.
Abstract : We describe Streptomyces fradiae mechanisms of sensitivity to nitrone‐oligomycin A, a derivative of oligomycin A. We obtained S. fradiae‐ nitR + bld, a nitrone‐oligomycin A resistant mutant with a «bald» phenotype. Comparative genomic analysis of the wild‐type S. fradiae ATCC19609 and S. fradiae ‐nitR + bld revealed a mutation in pa dR – a gene encoding a multifunction transcription regulator, which resulted in the amino acid replacement in a highly conserved DNA‐binding domain. Bioinformatics genome analysis of S. fradiae ATCC19609 discovered a PadR binding site 13 bp upstream the start codon of the marR transcription factor gene. Induction of S. fradiae nitR + bld and w.t. strains with nitrone‐oligomycin A lead to a significant increase in expression level of the marR gene in the w.t. strain, but no change observed in mutant strain. We identified differences between DNA–protein interactions of the mutant and native PadR proteins with its putative binding site in S. fradiae ATCC19609. This allowed us to suggest that the pa dR gene, that harbored a single nucleotide mutation in the S. fradiae nitR + bld strain, might be involved in the mechanism of resistance to nitrone‐oligomycin A. We assume the participation of the transcriptional factor pa dR in the formation of the bald phenotype.